Peru : Staff Report for the 2008 Article IV Consultation, Fourth Review and Inflation Consultation Under the Stand-By Arrangement and Request for Waiver of Applicability of Performance Criteria-Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Peru. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper presents the staff report for Peru's 2008 Article IV Consultation, Fourth Review and Inflation Consultation under the Stand-By Arrangement and request for waiver of applicability of performance criteria. Peru has been liberalizing external trade through tariff reductions in past years and has also been seeking enhanced market access through new bilateral agreements. There has been progress in simplifying administrative procedures and in enacting legislation to reduce labor market informality. The economy has been moderately affected by the global financial crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet